Hierarchical Fragmentation and Jet-like Outflows in IRDC G28.34+0.06: A Growing Massive Protostar Cluster - Wang, Ke; Zhang, Qizhou; Wu, Yuefang; Zhang, Huawei (The Astrophysical journal, 2011)
We present Submillimeter Array (SMA) Delta *l = 0.88 mm observations of an infrared dark cloud G28.34+0.06. Located in the quiescent southern part of the G28.34 cloud, the region of interest is a massive (>103 M ) molecular clump P1 with a luminosity of ~103 L , where our previous SMA observations at 1.3 mm have revealed a string of five dust cores of 22-64 M along the 1 pc IR-dark filament. The cores are well aligned at a position angle (P.A.) of 48? and regularly spaced at an average projected separation of 0.16 pc. The new high-resolution, high-sensitivity 0.88 mm image further resolves the five cores into 10 compact condensations of 1.4-10.6 M , with sizes of a few thousand AU. The spatial structure at clump (~1 pc) and core (~0.1 pc) scales indicates a hierarchical fragmentation. While the clump fragmentation is consistent with a cylindrical collapse, the observed fragment masses are much larger than the expected thermal Jeans masses. All the cores are driving CO (3-2) outflows up to 38 km s--1, the majority of which are bipolar, jet-like outflows. The moderate luminosity of the P1 clump sets a limit on the mass of protostars of 3-7 M . Because of the large reservoir of dense molecular gas in the immediate medium and ongoing accretion as evident by the jet-like outflows, we speculate that P1 will grow and eventually form a massive star cluster. This study provides a first glimpse of massive, clustered star formation that currently undergoes through an intermediate-mass stage.